The Bases of the Eurocentric Conception of History within the Framework of Western Knowledge, Positivism and Philosophy - Doğan Özlem (İnsan & Toplum)
Western philosophy and modern Western science regard themselves obliged to produce the knowledge of the universal in accordance with Platonian universalism. Therefore, singularist logic is paradoxical, completely remote from universalism and the principle of non-contradiction based on dia- lectical logic. That the West should evaluate singularist logic from its own viewpoint is understandable, however transforming this evaluation into a pejorative assessment and regarding cultures of the “Far East” and ancient Mediterranean-Mesopotamia as inferior to its own is a result of a definite unilateral and partial Eurocentrism. In this article, firstly, the Cartesian epistemology based on the philosophical roots of modern science born as a product of 17th century philosophy is analyzed. Secondly, positiv- ism is discussed as a philosophical movement, which helped realize the institutionalization of modern science being grounded more heavily upon an epistemological perspective, and came to the fore sup- porting the development of a political doctrine based upon modern science. The critiques by Hume and Kant aimed at modern epistemology for obliging philosophers addressing the question of knowledge without consulting metaphysical, theological and ethical patterns are referred to, and the effects of the developments occurring in the physical sciences, especially modern physics, on this debate are presented. In this context, the “universality” argument, which is one of links in the system of values and meanings used to reach a ““positive society”“, is assessed on the axis of the universalism-singularism debate and by taking into account universalist critiques.